Does metabolic syndrome or its component factors alter the course of bipolar disorder? A systematic review. (January 2022) - Giménez-Palomo, Anna; Gomes-da-Costa, Susana; Dodd, Seetal; Pachiarotti, Isabella; Verdolini, Norma; Vieta, Eduard; Berk, Michael
Highlights: Metabolic syndrome, obesity and impaired glucose metabolism can be considered risk factors for worse outcomes of bipolar disorder. Metabolic risk factors have been related to a chronic course of illness, worse global functioning and rapid cycling in bipolar disorder. Hypertension has not shown to have a significant impact on the course of bipolar disorder. Prevention strategies could lead to the improvement of both medical and psychiatric prognoses. Abstract: Metabolic syndrome (MetS) and its component factors, obesity, hypertension, dyslipidaemia and insulin resistance, have shown a bidirectional relationship with the prevalence and severity of bipolar disorder (BD). A systematic search of electronic databases (Pubmed, PsycINFO, clinicaltrials.gov) was conducted to explore and integrate current evidence about the role of MetS and its component factors with clinical outcomes of BD. Thirty-four articles met the inclusion criteria. Studies were grouped by the metabolic factors assessed, which included MetS, obesity and body mass index (BMI), dyslipidaemia, impaired glucose metabolism (IGM), diabetes mellitus and hypertension. They were then classified according to outcomes such as course of episodes, rapid cycling, suicidal behavior, treatment response, and global and cognitive functioning. Although current evidence remains controversial in most aspects of clinical outcomes, metabolic risk factors could alter the course of BD, with worse global functioning, poorer treatment response and a chronic course of illness, as well as enhancing rapid cycling. Further research is needed to elucidate the role of each risk factor in the mentioned outcomes.